Devonian and Carboniferous Brachiopods and Biostratigraphy of Transcaucasia - Alekseeva R.E.; Afanasjeva G.A.; Grechishnikova I.A.; Oleneva N.V.; Pakhnevich A.V. (My University, 2018)
The brachiopods of the orders Lingulida, Craniida, Orthida, Pentamerida, Rhynchonellida, Chonetida, Spiriferida, Spiriferinida, and Athyridida from the Middle–Upper Devonian and Lower Carboniferous of the Nakhchivan Autonomous Republic of the Republic of Azerbaijan and adjacent areas of Armenia are monographically described. The zonal scale for the Devonian and Carboniferous of Transcaucasia is elaborated based on the taxonomic composition and distribution of brachiopods and considering the data on the associated foraminifers, stromatoporoids, tabulate and rugose corals, tentaculites, bivalves, nautiloids, bryozoans, crinoids, conodonts, ostracods, trilobites, and f lora. The history of regional biostratigraphic studies is reviewed. The results of work enrich and specify paleontological substantiation of the stratigraphic and correlation scales of Transcaucasia and, in addition, are useful for covering the Devonian and Carboniferous stages of brachiopod evolution and for resolving the general issues of Paleozoic biostratigraphy, particularly, for the compiling the faunal characteristic of the Devonian–Carboniferous boundary deposits.
Keywords: Brachiopods; Transcaucasia; Paleozoic::Carboniferous; Paleozoic::Devonian; Палеозой::Девонская; Палеозой::Каменноугольная